Siirt battaniye tekniğinin üç boyutlu sanatsal tekstil nesnelere taşınması - Yalçın, Mine Beşen (My University, 2020)
SİİRT BATTANİYE TEKNİĞİNİN ÜÇ BOYUTLU SANATSALTEKSTİL NESNELERE TAŞINMASI “Siirt Battaniye Tekniğinin Üç Boyutlu Sanatsal Tekstil Nesnelere Taşınması”, başlıklı tezin ana amacı: Sanatsal nesne üretiminde, Siirt battaniyesinin desen yapma özelliğinin teknik olarak geliştirilmesi ve günümüzde değişik alanlarda kullanılabilirliğine deneysel katkı sağlamaktır. Yapılan araştırma dört bölümden oluşmaktadır. Birinci bölümde, “Giriş” başlığı altında, konuyla ilgili genel bilgilere yer verilmiştir. Çalışmanın ikinci bölümünde “Dokumacılığa Genel Bakış” başlığı altında, arkeolojik veriler ışığında dokumacılığın tarihsel gelişimi, Anadolu’da tiftik dokumacılığı ve Siirt battaniye dokumacılığının tarihi incelenmiştir. Siirt battaniyesinde temel malzemeler, araç gereçler, desen ve renk özelliklerine ayrıntılı bir şekilde yer verilmiştir. Siirt battaniyesinde dokuma tekniğinin işlem basamakları sırasıyla anlatılmıştır. Alan araştırması sırasında karşılaştığımız Siirt battaniye örneklerinin görsel ve fiziksel incelemeleri yapılarak, dokuma analiz tablosu oluşturulmuş ve bu tablolardaki veriler ile değerlendirilmiştir. Üçüncü bölümde, Siirt battaniyesinin teknik özellikleri irdelenerek, bu bilgiler ışığında “deneysel dokumalar” yapılmıştır. Desen, kalite, tarayarak oluşturulan desen denemeleri yapılmış ve deneysel dokuma önermeleri gerçekleştirilmiştir.Bu çalışmaların sonunda, “Sanatsal Arayışlar” başlığı altında, Siirt battaniye tekniğinin kullanıldığı araştırmacının kişisel uygulamalarına yer verilmiştir.Sonuç kısmında; geleneksel bir ürünün, üretim özelliklerinin hem hammaddeye, hem üretim sürecine hem de görsel estetiğine bağlı olan özelliklerinin, güncellenmesi gereği üzerinde durulmuştur. Bu iddiayı kanıtlamak üzere, deneysel çalışmalar, tasarımda kullanılabilir önermeler ve sanatsal denemeler ortaya konulmuştur. Tekstil tasarımcının geleneksel ve özgün ürünlere, sistematik bir bakışının, başta sanat ve tasarım çalışmalarına örnek olabileceği önerisi ve yeni sistematik yaklaşımların kişisel özgünlüklerle ortaya çıkabileceği öngörüsü ile tez tamamlanmıştır.

TRANSFERRİNG OF SİİRT BLANKET TECHNİQUE TO THREE DİMENSİONAL ARTİSTİC TEXTİLE OBJECTSThe main aim of the thesis titled Transferring of Siirt Blanket Technique to Three Dimensional Artistic Textile Objects is to develop the design feature of Siirt blanket in artistic object production and to contribute experimentally to its usage in different fields today.The research consists of four chapters.ın the first chapter,general informations which are related to topic have given under the “Introduction “section . In the second part of the study, the historical development of weaving in the light of archaeological data, the history of mohair weaving in Anatolia and Siirt blanket weaving were examined under the title of General Overview of Weaving. The basic materials, tools, pattern and color features of the Siirt blanket are given in detail. The steps of weaving technique in Siirt blanket are explained respectively. By making visual and physical examinations of Siirt blanket samples that we encountered during the field study, a weaving analysis table was created and evaluated with the data in these tables.In the third chapter, the technical features of the Siirt blanket are examined and experimental weavings are made in the light of this information. Pattern, quality, pattern created by combing have been tested and experimental weaving proposals have been realized.Researcher’s individual applications are included using by Siirt BlanketTechnique at the end of these studies which undertitle of “ArtisticSearches”In the conclusion part; It is focused that the production features of a traditional product should be updated, depending on the raw material, production process and visual aesthetics. In order to prove this claim, experimental studies, propositions that can be used in design and artistic essays have been put forward. The thesis has been completed with the suggestion that the textile designer's systematic approach to traditional and original products can be an example for art and design studies and with the prediction that new systematic approaches can be revealed with personal originality.Experimental weavings has been performed by examining technical features of Siirt Blankets In the chapter three by in the light of these examinations. proposal of experimental weavings, pattern, quality have been created & performed by combResearcher’s individual applications are included using by Siirt Blanket Technique at the end of these studies which under title of “Artistic Searches”In the conclusion part; It was emphasized that the features of a traditional product and its production features, which depend on the raw material, production process and visual aesthetics, should be updated.. Experimental exworks & Artistic experimentals has exhibited to prove this professing & proposals which can be used in design. The thesis has been completed with the suggestion that a systematic view of the Textile Designer on traditional and original products can be an example for other art and design works and with the prediction that new systematic approaches can emerge with personal originality.
Keywords: Angora Goat; Ankara Keçisi Textile; Dokuma; Fine arts education; Güzel sanatlar eğitimi; Mohair; Siirt Battaniyesi; Siirt Blanket; Tekstil; Textile; Tiftik; Weaving